ANALISIS DINAMIK MODEL MANGSA PEMANGSA DENGAN FUNGSI RESPON MICHAELIS MENTEN DAN PEMANENAN - Kridha Pusawidjayanti (UNIVERSITAS NEGERI MALANG, 2021)
The Predator-Prey model is an interesting study because it involves an ecosystem of two species that can provide benefits to human life. The purpose of this study was to determine the stability at the equilibrium points of the predator-prey model and the response function of Michaelis Menten and harvesting. This research method is a literature collection method that begins with the construction of the model, finds the equilibrium points, gets stability at the equilibrium points, then confirms the analytical result using numerical simulations. The predator-prey model with harvest assumptions and Michaelis Menten’s response function gets three equilibrium points, namely E_1, E_2, and E_3. E_1 and E_2 are asymptotically stable under certain conditions, while E_3 is unstable.